MICROBES AND MARKETS: WAS THE BLACK DEATH AN ECONOMIC REVOLUTION?. (13th May 2016) - Clark, Gregory
Abstract: Recent papers have suggested that the Industrial Revolution in Europe ultimately derives from the labor scarce economy of northwest Europe, which some trace back to the Black Death [Voigtländer and Voth (2013a ) and Allen (2011 )]. This paper examines the effects of the Black Death in England. Specifically, did it merely change relative factor prices, or did it lead to lasting gains in the efficiency of the economy after 1348? Extensive wage and price data from England 1210–1800 suggest that the population losses of the Black Death were associated with a surprising increase in economic efficiency, despite the decline in the scale of the economy. But this efficiency gain disappeared when population rose again in the 16th century. There is no sign of a connection between a labor scarce economy, and a switch to faster long run economic growth through technological advance.